Diagnostic Accuracy of Nasopharyngeal Swab Cultures in Children Less Than Five Years with Chronic Wet Cough - Ali A. Asseri; Nasim Khattab; Dima Ezmigna; Nabil J. Awadalla; Cori Daines; Wayne Morgan (MDPI AG, 2021)
Background: It is necessary to find a non-invasive and accurate procedure to predict persistent bacterial bronchitis (PBB) causative organisms and guide antibiotic therapy. The study objective was to compare the diagnostic accuracy of nasopharyngeal swab cultures with bronchoalveolar lavage (BAL) cultures in children with PBB. Methods: Nasopharyngeal swab and BAL fluid specimens were collected and cultured for bacterial pathogens prospectively from less than five-year-old children undergoing flexible bronchoscopy for chronic wet cough. Results: Of the 59 children included in the study, 26 (44.1%) patients had a positive BAL bacterial culture with neutrophilic inflammation. Prevalence of positive cultures for any of the four common respiratory pathogens implicated in PBB (Moraxella catarrhalis, Streptococcus pneumoniae, Staphylococcus aureus, and Haemophilus influenzae) was significantly higher (p = 0.001) in NP swabs compared to BAL fluids (86.4% and 44.1% of PBB cases, respectively). NP swab cultures for any of the four main bacterial pathogens had 85% (95% CI: 65-96%) and 48% (95% CI: 31-66%) sensitivity and specificity of detecting PBB, respectively. Positive and negative predictive values were 56% (95% CI: 47-65%) and 80% (95% CI: 60-91%), respectively. In conclusion, in children less than 5 years of age with chronic wet cough (PBB-clinical), a negative NP swab result reduces the likelihood of lower airway infection; however, a positive NP swab does not accurately predict the presence of lower airway pathogens. Flexible bronchoscopy should be considered in those with recurrent PBB-clinical or with clinical pointers of central airway anomalies.